Regional function-based land use balance - Nurhaidar, Wa Ode; Kurniawan, Surya; Gaffara, Ghefra Rizkan (Journal of Intelligent Decision Support System (IDSS), 2024)
The balance between the availability of land and the need for control, use and utilization of land based on regional functions is important as a reference for sustainable development directions and maintaining environmental sustainability. Imbalance in land use affects the direction of development and environmental sustainability. For this reason, it is necessary to conduct an analysis to determine the balance between land availability and land needs within a certain period of time through the preparation of a land use balance based on regional function directions. This research aims to analyze the balance between land availability and land use as well as the suitability of land use for the direction of regional functions. The method in this research uses a multi-temporal approach by utilizing remote sensing technology and geographic information systems. The overlay process was carried out to see the land change of Baubau city and see the level of conformity of existing land use with the direction of regional functions. The results show that the 2016 land use balance has the highest assets in forest land use of 21097.66 Ha and the 2020 land use balance has the highest liabilities in forest land use of 20959.56 Ha. The trend of land change in 2016-2020 is the change of forest, open land, mixed gardens, settlements and shrubs/shrubs. The level of conformity of existing land use with the direction of the function of the area is very high with a percentage level of suitability of 90.83% and a level of incompatibility of 9.17%.